Service Marketing Mix Factors that Affecting the Loyalty of Customer Who Using Welfare Shop at Royal Irrigation Department, Samsen, Bangkok - Ladnalao, Jirawan; Sukpun, Pordee (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were to study 1) opinions towards service marketing mix factors; 2) service marketing mix factors affecting customer loyalty of the Royal Irrigation Department welfare shop customers, Samsen, Bangkok. A sample group were 400 people including civil servants, permanent employees, temporary employees, and government employees of the Royal Irrigation Department, Samsen, Bangkok. A questionnaire was used to collect data. The statistics used were mean, standard deviation, and Multiple Regression Analysis. The results showed that 1) most of the respondents had opinions towards service marketing mix factors on marketing promotion, products and services, personnel, distribution channels, price, physical characteristics, and process at a high level. Also the level of opinions towards the loyalty of customers on word-of-mouth behavior, purchase intent, the sensitivity to price factors, and complaint behavior were at a high level. 2) The results of the analysis of service marketing mix factors affecting the loyalty of users showed that it can predict the loyalty of the Royal Irrigation Department's welfare shop customers with a statistically significance at the 0.05 level as follows: The word-of-mouth behavior was 50.1% (personnel (Beta=0.254), physical characteristics (Beta=0.242) and processes (Beta=0.240)). The sensitivity to price factors was 49.8% (personnel (Beta=0.357); distribution channel (Beta=0.207), price (Beta=0.145), and physical characteristics (Beta=0.136)); complaint behavior was 35.4% (personnel (Beta=0.305), and distribution channel (Beta=0.153)); and 34.3% of purchase intent (personnel (Beta=0.259), physical appearance (Beta=0.228), distribution channels (Beta=0.197).